Book Review: Chambers, Robert. 2017: Can We Know Better? Reflections for Development. (January 2019) - Cochrane, Logan
Chambers, Robert. 2017: Can We Know Better? Reflections for Development . Warwickshire: Practical Action Publishing. 194 pp. £9.45 (Paperback). ISBN: 9781853399459.